PEMBERDAYAAN MASYARAKAT DENGAN TEKNOLOGI SUMUR RESAPAN GUNA MENINGKATKAN KETERSEDIAAN AIR TANAH - Rhenny Ratnawati; indah nurhayati; Muhammad Al Kholif; Mochammad Shofwan (Jurnal Abadimas Adi Buana, 2019)
The purpose of the KKN-PPM activity is to make people aware of the importance of environmental conservation through groundwater conservation and empowering the people of Kalanganyar Village to build rainwater infiltration wells to help optimize water absorption. The output targets of the products produced in this program are: 1. Establishment of environmental cadres in the division of groundwater conservation as an effort to sustain the program, 2. Establishment of infiltration wells, and 3. Skills in maintaining infiltration wells. The method of implementation carried out is the preparation, debriefing and departure of KKN-PPM students, the development of appropriate technology (TTG), the implementation phase, and the assistance of environmentalcadres in the division of groundwater conservation. Conclusions from the KKN-PPM activities on groundwater conservation using infiltration wells in Kalanganyar Village, Sedati District, Sidoarjo Regency, East Java Province are: 1. The people of Kalanganyar Village have not used rainwater in the rainy season which caused rainwater runoff to flood and have limited water during the dry season, 2. Increasing knowledge of the people of Kalanganyar Village about environmental preservation and groundwater conservation using infiltration wells, 3. KKN-PPM Kalanganyar Village Sedati District Sidoarjo Regency provides a pilot in the form of infiltration wells in Kalanganyar Village to be used as a pilot for groundwater conservation in the village Kalanganyar.